2001
DOI: 10.1007/s004410100357
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of nitric oxide synthase and vasoactive intestinal polypeptide immunoreactivity in the sphincter of Oddi and duodenum of the possum

Abstract: The nitrergic innervation of the sphincter of Oddi (SO) and duodenum in the Australian brush-tailed possum and the possible association of this innervation with the neuropeptide vasoactive intestinal polypeptide (VIP) were investigated by using immunohistochemical localisation of nitric oxide synthase (NOS) and VIP, together with the general neuronal marker, protein gene product 9.5 (PGP9.5). Whole-mount preparations of the duodenum and attached SO without the mucosa, submucosa and circular muscle (n=12) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“…Recombinant human hemoglobin may alter the motor function of the sphincter of Oddi in vitro and in vivo by binding endogenous NO (Cullen et al, 1996). Neurons containing nNOS immunoreactivity or NADPH diaphorase were histochemically detected in the sphincter of Oddi of the human, monkey (De Giorgio et al, 1994), dog (Tanobe et al, 1995), guinea pig (Wells et al, 1995), and possum (Baker et al, 1993;Simula et al, 2001). The presence of NOS has also been demonstrated in the gall bladder and biliary pathways of the guinea pig (Grozdanovic et al, 1994), monkey, and human (De Giorgio et al, 1994;Uemura et al, 1997).…”
Section: E Sphincter Of Oddi and Gall Bladdermentioning
confidence: 98%
“…Recombinant human hemoglobin may alter the motor function of the sphincter of Oddi in vitro and in vivo by binding endogenous NO (Cullen et al, 1996). Neurons containing nNOS immunoreactivity or NADPH diaphorase were histochemically detected in the sphincter of Oddi of the human, monkey (De Giorgio et al, 1994), dog (Tanobe et al, 1995), guinea pig (Wells et al, 1995), and possum (Baker et al, 1993;Simula et al, 2001). The presence of NOS has also been demonstrated in the gall bladder and biliary pathways of the guinea pig (Grozdanovic et al, 1994), monkey, and human (De Giorgio et al, 1994;Uemura et al, 1997).…”
Section: E Sphincter Of Oddi and Gall Bladdermentioning
confidence: 98%
“…Our data also demonstrate that ATP activates a nitrergic pathway, which may involve interneurons or nitrergic motor neurons. Immunohistochemical studies have shown that NOS containing nerves are abundant in the SO [28,29]. Studies in guinea pig, pig, and human SO have suggested that nitric oxide is released tonically to inhibit contractile activity [30,31], therefore ATP may be involved in maintaining the tonic release of nitric oxide in the SO.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies demonstrated a relaxatory motor effect of NO on SO motor activity and the presence of NOS-IR inhibitory neurons. The study by Simula et al [33] demonstrates that the density of NOS-IR neurons is greater in the distal half of the SO myenteric plexus. Another interesting observation is that approximately 50% of all SO myenteric neurons were NOS-IR, consistent with a significant inhibitory drive to the SO.…”
Section: Neurotransmittersmentioning
confidence: 97%